2017
DOI: 10.1038/s41598-017-02334-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability in adolescent fMRI within two years – a comparison of three tasks

Abstract: Longitudinal developmental fMRI studies just recently began to focus on within-subject reliability using the intraclass coefficient (ICC). It remains largely unclear which degree of reliability can be achieved in developmental studies and whether this depends on the type of task used. Therefore, we aimed to systematically investigate the reliability of three well-classified tasks: an emotional attention, a cognitive control, and an intertemporal choice paradigm. We hypothesized to find higher reliability in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 61 publications
7
42
0
Order By: Relevance
“…The likelihood of this alternative account is supported by findings of differences in DMN activation in AN samples in various tasks involving self-perception and evaluation [69][70][71][72]. Last but not the least, regardless of which interpretation best fits the data, the observed longitudinal activation changes in a task with good group-level test-retest reliability [50] underlines the notion that DD might not be a static trait, as is often thought [76,77], but is rather a highly malleable and task-dependent process [78].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The likelihood of this alternative account is supported by findings of differences in DMN activation in AN samples in various tasks involving self-perception and evaluation [69][70][71][72]. Last but not the least, regardless of which interpretation best fits the data, the observed longitudinal activation changes in a task with good group-level test-retest reliability [50] underlines the notion that DD might not be a static trait, as is often thought [76,77], but is rather a highly malleable and task-dependent process [78].…”
Section: Discussionmentioning
confidence: 87%
“…Participants performed the same two-part DD task as in our previous cross-sectional fMRI studies [23,40], at both time points. The task has been shown to demonstrate an ability to distinguish between age groups known to differ in self-control [49] and an overall good test-retest reliability, both on a behavioral and neural level in adolescents [50]. Participants first performed a pre-scan calibration session, including 50 choices between a fixed smaller sooner (SS) reward (20 €) or a LL one to be paid after a delay (10, 30, 60, 120, or 180 days).…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 Although we found no evidence of alterations in weight-recovered participants with anorexia relative to healthy controls, it is important to keep in mind that activation may vary significantly between paradigms, 13,14 and the observed null effect may be task-specific. For example, although our task distinguished between individuals who differed in impulsivity, 16,56 the fact that it was designed to elicit equally frequent choices for immediate and delayed rewards may have masked our ability to detect subtle group differences. Another speculative explanation for the absence of group differences in brain function in the current weight-recovered/healthy controls sample might be that potential scar effects were not detectable in our relatively young sample with a relatively short duration of illness (Table 1) or normalization of brain structure following weight recovery.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, although the majority of studies that have examined the reliability or stability of reward task activation restricted their analyses to a priori reward-network ROIs, some looked beyond these structures. These studies have found that it is not uncommon for other regions of the brain to exhibit greater stability than the regions targeted by a task (i.e., regions in the default mode network have been frequently observed to be highly reliable) (Elliott et al, 2020;Fröhner et al, 2019;Holiga et al, 2018;Keren et al, 2018;Vetter et al, 2017). It is possible that regions performing computations not directly manipulated by the task may exhibit more stable inter-trial activation patterns, resulting in increased stability.…”
Section: Additional Factors Influencing Stabilitymentioning
confidence: 99%